Peran Personal Digital Archiving Dalam Preservasi Arsip Orkes Keroncong Surya Mataram Yogyakarta - Artanto, Mei (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2023)
The current state of the physical release of the Orkes Keroncong Surya Mataram tape, with limited quantity and inadequate archival practices, require an urgent digitization and management initiative. The objective of this activity is to ensure that the succeeding generations inherit a comprehensive understanding of keroncong music from the Orkes Keroncong Surya Mataram. This research seeks to comprehend the process of digitizing and managing the audio digital archive of the Orkes Keroncong Surya Mataram, employing the principles of personal digital archiving for preservation. A qualitative research with utilizing a case study approach was employed to identify the process of digitizing physical assets such as tape tapes, Orkes Keroncong Surya Mataram tapes, and managing digital archives as preservation efforts. This involved selecting a social situation, employing data collection techniques, and undertaking data analysis processes. The findings of this study reveal that there are 44 songs across four tape cassettes in optimal condition for digitization. The digitization process is executed through three stages: preparation, implementation, and archiving. Once digitized, the 44 songs are managed based on the principles of personal digital archiving. In conclusion, personal digital archiving plays a crucial role in preserving and managing information pertaining to the intra-aesthetic value of keroncong music, serving as a valuable source of knowledge and future research data. Based on the research findings, digital archivists personally extend recommendations to individuals, groups, and the general public, emphasizing the importance of proper and wise archival care. The use of technology and the internet facilitates easier implementation and access to the results of personal digital archiving efforts.